Mitochondrial ferredoxin determines vulnerability of cells to copper excess - Vallières, Cindy; Holland, Sara L.; Avery, Simon V. (Elsevier, 2017)
The essential micronutrient copper is tightly regulated in organisms, as environmental exposure or homeostasis defects can cause toxicity and neurodegenerative disease. The principal target(s) of copper toxicity have not been pinpointed, but one key effect is impaired supply of iron-sulphur (FeS) clusters to the essential protein Rli1 (ABCE1). Here, to find upstream FeS-biosynthesis/delivery protein(s) responsible for this, we compared copper sensitivity of yeast overexpressing candidate targets. Overexpression of the mitochondrial ferredoxin Yah1 produced copper hyper-resistance. 55Fe turnover assays revealed that FeS1-integrity of Yah1 was particularly vulnerable to copper among the test proteins. Furthermore, destabilization of the FeS domain of Yah1 produced copper hypersensitivity, and YAH1 overexpression rescued Rli1 dysfunction. This copper-resistance function was conserved in the human ferredoxin, Fdx2. The data indicate that the essential mitochondrial ferredoxin is an important copper target, determining a tipping point where plentiful copper supply becomes excess. This knowledge could help in tackling copper-related diseases.